Functional and quantitative magnetic resonance myelography of symptomatic stenoses of the lumbar spine - Eberhardt, Knut; Ganslandt, Oliver Thomas; Stadlbauer, Andreas (Neuroradiology, 2014)
The objective of this study was to demonstrate that functional, quantitative magnetic resonance myelography (MRM) allows standardized diagnosis of symptomatic lumbar spinal stenoses which show at least equal detectability compared to functional myelography and postmyelographic CT (pmCT) based on intra- and postoperative findings.We investigated 43 volunteers and 47 patients with symptomatic lumbar spinal stenoses using MRM in normal position as well as in flexion and extension in a standard whole-body MR scanner. Twenty volunteers were additionally examined under axial loading. All patients were investigated by functional myelography and pmCT and 10 patients had a functional lumbar MRM postoperatively. Range of motion and cerebrospinal fluid (CSF) volumes in normal position, flexion, extension, and under axial loading (volunteers) were assessed for each segment. Detectability was determined by using intraoperative findings, and postoperative freedom of symptoms was correlated with CSF volume changes in MRM.The ranges of motion in a standard whole-body MR scanner provide adequate scope for investigations into function (flexion and extension) in both volunteers and patients. Axial loading was associated with a mechanism of extension, albeit to a far smaller extent. Detectability of lumbar stenoses was 100% for MRM, 58% for conventional myelography, and 68% for pmCT. Postoperative changes in CSF volume of levels with stenoses in MRM strongly correlated with freedom of symptoms (R = 0.772).This MRM method allows for exact diagnosis and reproducible quantification of stenoses, motion-related changes, and spondylolistheses of the lumbar spine. It may be useful for early detection of alterations in order to avoid neuronal compression.
EVALuna2:22847